Dari Layar ke Hati: Efektivitas Nonton Bareng dalam Mengubah Persepsi terhadap Bullying dan Narkoba di Kalangan Remaja - Wannur, Zaim; Nasution, Edi Syahputra; Sitepu, Juli Maini (Journal of Community Sustainability, 2024)
Community service in Baru Village, Pulau Rakyat District, Asahan Regency aims to improve the quality of life of the community through education and empowerment programs. This study used a qualitative descriptive method with a participatory approach, involving 14 students for 21 days. Data were collected through participant observation, interviews, FGDs, and documentation. The results showed a significant increase in awareness of education and religion, public health, environmental cleanliness, and potential for economic empowerment. Education programs in schools and MDA increased active student participation, while religious activities strengthened Islamic values ​​in the community. Health and environmental cleanliness activities encouraged a healthy lifestyle and environmental awareness. Collaboration between the team, village government, and community was the key to the success of the program. Challenges such as time constraints and unpredictable weather were overcome through effective adaptation and management. Recommendations include follow-up programs, local cadre training, long-term collaboration, and periodic evaluation to ensure the sustainability of positive impacts in Baru Village.